Pelatihan Bahasa Arab Dasar untuk Ummahāt di Komunitas Berbagi Muslimah Indonesia (KBMI) - Hakim, Rahman; Azimah, Nahdliyyatul (Universitas Teuku Umar, 2025)
Arabic plays a highly transcendental role in the lives of Muslims, especially ummahāt. One form of community service aimed at improving their proficiency in basic Arabic is the provision of intensive Linguaphone audio training. This training is designed to equip ummahāt with the ability to master basic Arabic skills. The methods employed include lectures, listening activities, practice, and feedback. Data were collected through observation and interviews conducted via Google Forms. The research subjects consisted of 10 ummahāt who participated in a basic-level training program for one month, from 22 September to 20 October 2025. The results of the training indicate that: (1) Linguaphone audio serves as the primary learning tool for ummahāt in understanding the learning materials, such as correct pronunciation of hijaiyah letters, vocabulary, expressions, and dialogues; (2) Linguaphone audio is an efficient learning medium in terms of time, energy, and cost; and (3) ummahāt greatly benefited from the basic Arabic language training program using Linguaphone audio, particularly those who had never participated in a tahsin program and were beginner learners of Arabic.